Opening the Door? : Belarusian Art Today. - Kuizinas, Kestuti; Fomina, Julija; Prents, Lena; Shparaga, Olga; Exhibition. Opening the Door ? : Belarusian Art Today. Vilnius. Contemporary Art Centre Vilnius. 2010-11-18. 2011-01-09 (Vilnius : Contemporary Art Centre Vilnius, 2010)
Chkolnikova, Anna ; Davidovich, Lena ; Gourinovitch, Oxana ; Klinau, Artur ; Komarov, Aleksander ; Korablev, Aleksander ; Lunev, Alexei ; Naprushkina, Marina ; Peshekhonov, Igor ; Positive Actions ; Savchenko, Igor ; Shabohin, Sergei ; Shinkarenko, Aleksei ; Tschmyr, Philippe ; Belarusian Climate ; Tsesler, Vladimir ; Voichenko, Sergey ; Tyminko, Maxim ; Vashkevich, Ruslan ; Yushko, Oleg
biog. p. 136-137
Engels
Russisch
boek
Keywords: Wit-Rusland